A study on the effectiveness of eggshell as an abrasive agent in toothpaste - Mohd Zulkarnain, Nur Azurah Zuraikha; Veny, Harumi; Ab Hamid, Farah Hanim; Sazali, Rozana Azrina; Abd Rashid, Zulkifli; Alias, Azil Bahari (Universiti Teknologi MARA Shah Alam, 2025)
Growing concerns about the safety of synthetic ingredients in dental products have led to the search for natural alternatives. This study explores the potential of using eggshell as a calcium-rich byproduct of the food industry as a sustainable toothpaste ingredient. Eggshell powder, with its high content of calcium carbonate, was used in addition to a toothpaste base and its physicochemical properties were analysed using FTIR, XRD, and XRF. The formulated toothpaste was then tested for % calcium content, pH, foaming ability, and abrasiveness, with results compared to a commercial toothpaste. The eggshell-based toothpaste had 93.51 % calcium, a slightly alkaline pH of 8.05 and produced 14 mL of foam. The value was roughly 16.7 % more than that produced by the commercial one, which was 12 mL. Its moderate abrasiveness mimics the cleaning performance of conventional formulations, which suggests safe and effective cleaning performance. These results demonstrate that the eggshell powder can be used as a viable and eco-friendly alternative to synthetic fillers in toothpaste that would have functional properties while helping to reduce waste from the food industry.